Progress in Medicinal Chemistry. - Witty, D. R. (David R.); Cox, Brian (Progress in Medicinal Chemistry, 2018)
Progress in Medicinal Chemistry, Volume 57, provides a review of eclectic developments in medicinal chemistry, with this volume including chapters on the CaSR field, CFTR modulators in cystic fibrosis, macrocycles, VMAT2 inhibitors, and Big Data in Drug Discovery.